2020
DOI: 10.19080/ctoij.2020.15.555917
|View full text |Cite
|
Sign up to set email alerts
|

Target Volume Definition for Stereotactic Radiosurgery (SRS) Of Cerebral Cavernous Malformations (CCMS)

Abstract: Objective: Cerebral cavernous malformations (CCMs) are composed of abnormal hyalinized capillary clusters typically surrounded by deposits of hemosiderin. These vascular abnormalities of the brain may be asymptomatic, however, a plethora of symptoms may occur in some of the affected patients including seizures, hemorrhages, and neurological deficits. Stereotactic radiosurgery (SRS) has been utilized as a noninvasive modality of management for selected patients with high risk CCMs located at eloquent brain regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In this context, multimodality imaging may add to the accuracy of target definition for radiosurgery of intracranial GCTs. Indeed several other studies have demonstrated refined treatment volume determination by including MRI to the process of target determination [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, multimodality imaging may add to the accuracy of target definition for radiosurgery of intracranial GCTs. Indeed several other studies have demonstrated refined treatment volume determination by including MRI to the process of target determination [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, incorporation of multimodality imaging can be used for improving the precision of target localization, and integrated use of fused CT and MR images can facilitate optimization of treatment volume designation for successful RT applications. Indeed, several studies addressed the utility of multmodality imaging for RT target definition [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Our study may add to the literature given the limited data regarding the utility of multimodality imaging based target definition for irradiation of hemangiopericytomas.…”
Section: Discussionmentioning
confidence: 99%